2023
DOI: 10.5458/jag.jag.jag-2022_0013
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Dextran α-1,2-Debranching Enzyme from <i>Microbacterium dextranolyticum</i>

Abstract: Dextran α-1,2-debranching enzyme (DDE) releases glucose with hydrolyzing α-(1→2)-glucosidic linkages in α-glucans, which are made up of dextran with α-(1→2)-branches and are generated by Leuconostoc bacteria. DDE was isolated from Microbacterium dextranolyticum (formerly known as Flavobacterium sp. M-73) 40 years ago, although the amino acid sequence of the enzyme has not been determined. Herein, we found a gene for this enzyme based on the partial amino acid sequences from native DDE and characterized the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…EPSs have been demonstrated to play a crucial role in bacterial colonization, adherence, stress resistance, host–bacterium interactions, and immunomodulation ( 72 ). This study provided insight into the mechanism of α-(1→2)- and α-(1→3)-branched dextran degradation by Gram-negative bacteria, which is different from that of α-(1→2)-branched dextran degradation by the Gram-positive bacterium M. dextranolyticum ( 34 ). M. dextranolyticum removes α-(1→2) branches extracellularly, degrades dextran, and uptakes isomaltooligosaccharides into the cytosol, whereas F. johnsoniae extracellularly degrades branched dextran to oligosaccharides (with branches) and hydrolyzes all linkages, including branches, in the periplasm.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…EPSs have been demonstrated to play a crucial role in bacterial colonization, adherence, stress resistance, host–bacterium interactions, and immunomodulation ( 72 ). This study provided insight into the mechanism of α-(1→2)- and α-(1→3)-branched dextran degradation by Gram-negative bacteria, which is different from that of α-(1→2)-branched dextran degradation by the Gram-positive bacterium M. dextranolyticum ( 34 ). M. dextranolyticum removes α-(1→2) branches extracellularly, degrades dextran, and uptakes isomaltooligosaccharides into the cytosol, whereas F. johnsoniae extracellularly degrades branched dextran to oligosaccharides (with branches) and hydrolyzes all linkages, including branches, in the periplasm.…”
Section: Discussionmentioning
confidence: 93%
“…L. citreum S-32 and S-64 strains, which were isolated from the lines of a sugar-manufacturing factory, synthesize branched α-glucan. 13 C-NMR analysis revealed that S-32 α-glucan contains 30% α-(1→3)-linkages in addition to α-(1→6)-linkages; moreover, enzyme digestion analysis showed that it contains α-(1→2)-linked glucose ( 33 , 34 ). By contrast, S-64 α-glucan contains 24% α-(1→2)-, 24% of α-(1→3)-, and 9% of α-(1→4)-linkages ( 33 , 34 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation